Análise comparativa de orçamento por meio de SINAPI e de preços do comércio local em cidade de pequeno porte - Makimori, Milena Mayumi Costa (2023)
The budget plays a fundamental role in the realization of a project, as well as in all stages of a construction project. It is therefore extremely important to carry out research in this area, more specifically in the public sector, which defines its budgets using SINAPI, requiring knowledge of the particularities of each project, to use the data correctly according to each local reality. It was then noted the importance of carrying out a case study in the Midwest region of Paraná, in order to ascertain the applicability of the database. The aim of this study was therefore to compare a budget made using data from the SINAPI system and a budget using prices from local businesses, checking the final value of the two estimates and also the unit prices of inputs and services separately. After gaining access to the documents for a public building project in a small town, the breakdown of all the services that make up the base budget has begun. A survey of local businesses was then carried out to define unit prices and a study of collective bargaining agreements to calculate the hourly cost of labor. In this way, it was possible to draw up a budget with prices in the city under study. Once the final total value of the two budgets was obtained, it was found that the SINAPI budget was higher than the local one. Approximately half of the materials had a higher unit price with SINAPI, as did all the equipment and labor. The result of the comparison between final values is linked to the unit prices and service compositions.